Dividend Policy Ratios and Firm Performance: a case study of Selected Hotels & Restaurants in Sri Lanka - Priya, K.; Nimalathasan, B. (My University, 2013)
Dividend policy is one of the most complex aspects in finance. The reality is that dividend policy is more commonly an instrument of wealth distribution than it is an instrument of wealth creation. The study of firm performance determinants is a central question for strategic management. In this study, an attempt has been made to analyze the Dividend policy Ratios and Firm Performance during 2008 to 2012 (05 years) financial year of Selected Hotels & Restaurants in Sri Lanka. For the purpose of this study, the data was extracted from the annual reports of sample companies. Correlation and multiple regression analysis are used for analysis. The results revealed that dividend policy ratios has a great impact on all firm performance ratios except return on investment (ROI) and return on equity (ROE).Further EPS, P/E and PB are significantly correlated with ROA 5 percent level of significance. At the same time P/E is significantly correlated with ROE at 5 percent level of significance. Finally EPS and PB are significantly correlated with ROE at 1 percent level of significance.
Keywords: Dividend Policy; Firm Performance; Dividend Policy Ratios